2016
DOI: 10.1002/jts.22119
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder in U.S. Military Primary Care: Trajectories and Predictors of One‐Year Prognosis

Abstract: We examined the longitudinal course of primary care patients in the active duty Army with posttraumatic stress disorder (PTSD) and identified prognostic indicators of PTSD severity. Data were drawn from a 6-site randomized trial of collaborative primary care for PTSD and dpression in the military. Subjects were 474 soldiers with PTSD (scores ≥ 50 on the PTSD Checklist -Civilian Version). Four assessments were completed at U.S. Army installations: baseline, and follow-ups at 3 months (92.8% response rate [RR]),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Our results showed that PTSD is a chronic disorder that does not subside with time ( 6 , 34 ). Higher combat exposure was associated with more intense re-experiencing, negativity and hyperarousal, and depression, supporting the view that it predicts PTSD persistence ( 35 ). A previous study in Croatian veterans found that all PTSD symptoms were more severe with more intense war experience, but it did not assess depression and negativity and participants were exclusively prisoners of war ( 2 ).…”
Section: Discussionsupporting
confidence: 54%
“…Our results showed that PTSD is a chronic disorder that does not subside with time ( 6 , 34 ). Higher combat exposure was associated with more intense re-experiencing, negativity and hyperarousal, and depression, supporting the view that it predicts PTSD persistence ( 35 ). A previous study in Croatian veterans found that all PTSD symptoms were more severe with more intense war experience, but it did not assess depression and negativity and participants were exclusively prisoners of war ( 2 ).…”
Section: Discussionsupporting
confidence: 54%
“…We created one large record for each study that included data from all associated publications. Seventy studies reported in 84 publications are included in this review: Acierno et al, 2017;Agha, 2008;Badour et al, 2012;Belsher et al, 2012;Boden et al, 2013;Bonn-Miller et al, 2013;Bray et al, 2016;Creamer et al, 2002;Currier, Holland, and Drescher, 2014;DeViva et al, 2017;Elliott et al, 2005;Engel et al, 2015;Evans et al, 2010;Evans, Cowlishaw, and Hopwood, 2009;Foa et al, 2018;Fontana and Rosenheck, 1997;Fontana and Rosenheck, 1998;Fontana, Ford, and Rosenheck, 2003;Forbes et al, 2003;Forbes et al, 2005;Forbes et al, 2008;Forbes et al, 2010;Ford, Fisher, and Larson, 1997;Fortney et al, 2015;Friedman et al, 2007;Gallegos et al, 2015;Gallegos, Streltzov, and Stecker, 2016;Garcia et al, 2011;Gilman, Schumm, and Chard, 2012;Graca, Palmer, and Occhietti, 2014;Gros et al, 2013;Gros et al, 2018;Gros, Yoder, et al, 2011;Haller et al, 2016;Hebenstreit et al, 2015;Hernandez-Tejada et al, 2014;Hobfoll et al, 2016;…”
Section: Results Of the Searchmentioning
confidence: 99%
“…Heterogeneity was substantial (I 2 = 78%) and significant (p = .01). Thirteen studies (Belsher, 2012;Bray et al, 2016;Currier, 2014;Holder et al, 2018;Jeffreys et al, 2014;López et al, 2017;McLay et al, 2016;Tiet et al, 2015;Tuerk et al, 2011;Walter et al, 2014) Korte et al, 2017, included age in a path model and found older age associated with greater severity as measured by PCL scores (coefficient = 0.37) at the midtreatment point. Bray et al, 2016, found patients 35 years and older less likely to be classified as "improvers" at discharge (OR = 0.49, 95% [CI 0.24, 0.99]).…”
Section: Agementioning
confidence: 99%
See 2 more Smart Citations